Calibration 7" – Cutthroat Flume as New Size for Discharge Measurement at Free Flow Condition - Jaafar Maatooq; Muna Ibraheem (Engineering and Technology Journal, 2020)
This paper aims to conduct a series of laboratory experiments in case of steady-state flow for the new size 7 ̋ throat width (not presented before) of the cutthroat flume. For this size, five different lengths were adopted 0.535, 0.46, 0.40, 0.325 and 0.27m these lengths were adopted based on the limitations of the available flume. The experimental program has been followed to investigate the hydraulic characteristic and introducing the calibrated formula for free flow application within the discharge ranged between 0.006 and 0.025 m3/s. The calibration result showed that, under suitable operation conditions, the suggested empirical formulas can accurately predict the values of discharge within an error ± 3%.